2014
DOI: 10.1016/j.cellsig.2014.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy eliminates cytoplasmic β-catenin and NICD to promote the cardiac differentiation of P19CL6 cells

Abstract: Autophagy plays important roles in adipogenesis and neuron development. However, how autophagy contributes to cardiac development is not well understood. The main aim of our study was to determine the association between autophagy and myocardial differentiation and its roles in this process. Using a well-established in vitro cardiomyocyte differentiation system, P19CL6 cells, we found that autophagy occurred from the early stage of cardiac differentiation. Blocking autophagy by knocking-down of autophagy-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 37 publications
3
44
1
Order By: Relevance
“…Recent studies have shown that β-catenin signaling may play a role in autophagy in some models [10,11,12,13,14,15], whereas its involvement in autophagy in prostate cancer cells has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that β-catenin signaling may play a role in autophagy in some models [10,11,12,13,14,15], whereas its involvement in autophagy in prostate cancer cells has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, our knowledge on these contexts is rather limited. Recent studies have shown that Wnt/β-catenin signaling plays a role in autophagy in some models [10,11,12,13,14,15], but the involvement of this pathway in prostate cancer has not been reported. The Wnt signaling pathways are a group of signaling pathways that have been catalogued as the canonical Wnt pathway, the noncanonical planar cell polarity pathway and the noncanonical Wnt/calcium pathway.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with previous reports showing the loss of autophagy leads to the activation of the Notch signaling in Drosophila oogenesis 25 and autophagy eliminates cytoplasmic NICD to promote cardiac differentiation. 26 Autophagy is activated by mammalian target of rapamycin protein kinase pathway (mTOR). 41 mTOR is a center of autophagy regulation molecule, which is inhibited autophagy associated gene(ATG) to regulate autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Therefore, we investigate whether Notch1 signaling pathway can be regulated by autophagy during the biliary differentiation of WB-F344 cells. We also examine the effect of 2 autophagy stimuli, the mTOR inhibitor rapamycin and nutrient deprivation medium, on the biliary differentiation of WB-F344 cells.…”
Section: Autophagy Inhibits Notch1 Signaling Pathway During the Biliamentioning
confidence: 99%
See 1 more Smart Citation